2019
DOI: 10.1021/acsami.8b17300
|View full text |Cite
|
Sign up to set email alerts
|

Ultracompact, Well-Packed Perovskite Flat Crystals: Preparation and Application in Planar Solar Cells with High Efficiency and Humidity Tolerance

Abstract: Planar perovskite solar cells (PSCs) have exhibited a promising alternative for high efficiency recently because of a new record of certified power conversion efficiency (PCE) of 21.5%. At the present stage of PSCs, achieving further improvements for long-term stability and efficiency are the key issues. It is necessary to fabricate PSCs with good interface and film crystallinity. Here, planar PSCs are fabricated by a synergistic effect of dimethyl sulfoxide additive and a dropwise addition method in a two-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…Figure a–e shows samples A, B, C, D, and E in the top view, respectively, and the corresponding grain size distribution maps are accurately analyzed and shown in their insets. Generally, their surfaces are all blocklike and smooth, in accordance with the characteristics in the literature . It is clear that the size of the perovskite crystal obviously changes with different bismuthene contents, and the average grain sizes of samples A, B, C, D, and E are measured as 0.82, 0.94, 1.02, 0.97, and 0.96 μm, respectively.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Figure a–e shows samples A, B, C, D, and E in the top view, respectively, and the corresponding grain size distribution maps are accurately analyzed and shown in their insets. Generally, their surfaces are all blocklike and smooth, in accordance with the characteristics in the literature . It is clear that the size of the perovskite crystal obviously changes with different bismuthene contents, and the average grain sizes of samples A, B, C, D, and E are measured as 0.82, 0.94, 1.02, 0.97, and 0.96 μm, respectively.…”
Section: Resultssupporting
confidence: 85%
“…These require complex technologies and an expensive processing environment. In addition, a PCE of 20.63% with only 0.03 hysteresis was also achieved with the SnO 2 ETL in our previous work . To achieve high PCE, a dropwise addition method is employed to subtly fabricate the perovskite layer for achieving larger grain sizes.…”
Section: Introductionmentioning
confidence: 84%
“…5 b, with the equivalent circuit model displayed in the inset. Here, R s represents the series resistance, which primarily reflects the electrical contacts, wires, and sheet resistance of the electrodes [ 53 ]. The charge-transfer properties at the interface are reflected by the charge-transfer resistance ( R tr ), whereas R rec is related to the recombination of the carriers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The series resistance (R s ) mainly reflects electrical contacts, wires, and sheet resistance of the electrodes [43,53]. The charge-transfer resistance (R tr ) means the charge-transfer property at the interface, and R rec means the recombination of carriers [43,54]. Fitted with ZView software, it can be observed that the R s values are similar for these samples.…”
Section: Resultsmentioning
confidence: 99%
“…The perovskite layer with (FAPbI 3 ) 0.97 (MAPbBr 3 ) 0.03 was fabricated on the ETL by a two-step deposition strategy as described in our previous work [ 21 , 43 ]. In belief, 1.3 M PbI 2 in the mixture solvent of DMF/DMSO (9.5:0.5, by volume) was spin-coated onto the ETL at 1500 rpm for 30 s and then annealed at 70 °C for 1 min in N 2 atmosphere in a glove box.…”
Section: Methodsmentioning
confidence: 99%